Strengthening Higher-Order Thinking in Science Through Collaborative Gameplay: A Quasi-Experimental Study - Oro, Cheryl P.; Narsico, Peter G.; Napoles, Janine; Reyes, Heart Love S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The K–12 science curriculum emphasizes the development of essential 21st-century skills such as critical problem-solving, environmental literacy, innovation, and effective communication. Despite these curricular priorities, traditional lecture-based instruction often fails to cultivate higher-order thinking—particularly logical reasoning, which is foundational in science learning. This study investigates the effectiveness of Collaborative Game-Based Activities (CGBAs) as an instructional strategy to enhance students’ logical reasoning skills in science. Employing a quasi-experimental research design, the study assessed the quality of CGBA implementation, students’ baseline competency in logical reasoning, their progress across successive CGBA sessions, and overall improvement after the intervention. Grade 9 students participated in a series of CGBA sessions, with their logical reasoning abilities evaluated through pre-test and post-test assessments. Teacher rubric-based evaluations of CGBA quality revealed consistently high implementation fidelity, aligning well with instructional objectives. The findings indicated a significant improvement in students’ logical reasoning scores following CGBA exposure, with the majority advancing from “Satisfactory” to “Good” and “Very Good” performance levels. A paired-samples t-test confirmed this difference to be statistically significant (p < .001), supporting the intervention’s impact on academic performance. The study also affirmed that the assumptions required for parametric testing were met, enhancing the reliability of the findings. Overall, the study underscores the pedagogical value of integrating collaborative and game-based approaches to foster critical thinking, teamwork, and deep engagement with scientific concepts. By transforming passive instruction into active, inquiry-driven learning, CGBA offers a compelling model for strengthening logical reasoning and promoting meaningful science education.